Periodicity of the Positive Solutions of a Fuzzy Max-Difference Equation - Qiuli He; Chunyan Tao; Taixiang Sun; Xinhe Liu; Dongwei Su (Abstract and Applied Analysis)
We investigate the periodic nature of the positive solutions of the fuzzy max-difference equation xn+1=maxAn/xn-m,xn-k,n=0,1,…, where k,m∈{1,2,…}, An is a periodic sequence of fuzzy numbers, and x-d,x-d+1,…,x0 are positive fuzzy numbers with d=m,k. We show that every positive solution of this equation is eventually periodic with period k+1.